ANALISIS POWER OTOT LENGAN, KELENTUKAN DAN KOORDINASI MATA-TANGAN TERHADAP PUKULAN LOB PERMAINAN BULUTANGKIS - Muhammad Haekal; Hasan Basri (PARADIGMA : JURNAL ILMU PENGETAHUAN AGAMA, DAN BUDAYA, 2021)
This article aims to determine the components of arm muscle power and eye-hand coordination on lob shots in badminton. The method used in analyzing it is in the form of library research. Collecting data on this article through an article indexing engine, namely Google Scholar with the keywords arm muscle power, hand eye coordination, lob strokes in badminton with publication limits from 2016 to 2020. The results obtained from 30 journals reviewed showed that the component of the lob stroke badminton is, speed, accuracy, agility and power. The contribution of each component varies greatly to produce a good technique for a badminton athlete. Conclusions from 30 that have been reviewed show that the needs for the lob component of badminton players are speed, accuracy, agility and maximum power. Each component must function optimally to support an athlete in official and unofficial competitions.